Wealth: A Family Matter - Bessière, Céline; Pugliese, Maude (Enfances, Familles, Générations, 2024)
Research framework: Over the past decade, social science research has been profoundly renewed by the measurement of socioeconomic inequalities, which no longer takes into account only socio-professional status, labor income, or qualifications, but also wealth. Family matters for inheriting wealth, saving it, or accumulating it through returns on investments. The accumulation of wealth brings into play the three major dimensions of kinship: descent, siblingship, and alliance. Objectives: To establish a dialogue between the literature on socio-economic inequalities and the social sciences of the family. Methodology: This introductory article is based on a literature review of various social science disciplines in economics, sociology, demography, history, anthropology, political philosophy and law. Results: This issue of the journal Enfances Familles Générations is a plea for the social sciences to take into account both family ties and family assets, based on the concrete issues of inheritance, marriage, indebtedness and home ownership. Inheritance, its accumulation, preservation and transmission are, in fact, concerns within families of all social backgrounds. Conclusion: Family dynamics - in interaction with the multiple actors in the family field - play a part in structuring economic inequalities within the family (especially gender inequalities) and between families (especially class- and race-based inequalities). But exploring inequalities in asset and debt also provides a better understanding of family relationships, since wealth participates in the making of the family. Contribution: This introductory article affirms the importance of studying family wealth strategies across all social classes, and of multiplying the historical, national and cultural contexts of study.